2019
DOI: 10.1523/jneurosci.3188-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Homer1a Is Required for Establishment of Contralateral Bias and Maintenance of Ocular Dominance in Mouse Visual Cortex

Abstract: It is well established across many species that neurons in the primary visual cortex (V1) display preference for visual input from one eye or the other, which is termed ocular dominance (OD). In rodents, V1 neurons exhibit a strong bias toward the contralateral eye. Molecular mechanisms of how OD is established and later maintained by plastic changes are largely unknown. Here we report a novel role of an activity-dependent immediate early gene Homer1a (H1a) in these processes. Using both sexes of H1a knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Another curious set of findings are that the suggested homeostatic role of Homer 1a (an immediately early gene) in establishing the innate contralateral eye bias in mice is independent of visual experience, but necessary for OD changes in the long-term (5-6 days) MD and unnecessary for the short-term (2-3 days) MD effects (Choski, Druciak, Worley, & Lee, 2019). It must be pointed out that in mice, the duration of MD for 4 days or longer is usually needed for the clear and thus stable changes in the OD distribution (Gordon & Stryker, 1996; see also Table 1).…”
Section: Excitation-inhibition Balance-roles Of Gaba System and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Another curious set of findings are that the suggested homeostatic role of Homer 1a (an immediately early gene) in establishing the innate contralateral eye bias in mice is independent of visual experience, but necessary for OD changes in the long-term (5-6 days) MD and unnecessary for the short-term (2-3 days) MD effects (Choski, Druciak, Worley, & Lee, 2019). It must be pointed out that in mice, the duration of MD for 4 days or longer is usually needed for the clear and thus stable changes in the OD distribution (Gordon & Stryker, 1996; see also Table 1).…”
Section: Excitation-inhibition Balance-roles Of Gaba System and Beyondmentioning
confidence: 99%
“…In postsynaptic density (PSD)‐95 knock‐out mice, an instructive role of PSD‐95 in opening and closing the critical period was shown, as expressed in the maturation of “silent” glutamatergic synapses, largely independent of the inhibitory tone (Huang et al, 2015). Another curious set of findings are that the suggested homeostatic role of Homer 1a (an immediately early gene) in establishing the innate contralateral eye bias in mice is independent of visual experience, but necessary for OD changes in the long‐term (5–6 days) MD and unnecessary for the short‐term (2–3 days) MD effects (Choski, Druciak, Worley, & Lee, 2019). It must be pointed out that in mice, the duration of MD for 4 days or longer is usually needed for the clear and thus stable changes in the OD distribution (Gordon & Stryker, 1996; see also Table 1).…”
Section: Excitation‐inhibition Balance—roles Of Gaba System and Beyondmentioning
confidence: 99%
“…It is possible that distinct cellular mechanisms differentially regulate contralateral and ipsilateral responses and plasticity. For example, it has recently been shown that Homer1a specifically and actively establishes the contralateral bias intrinsic to binocular-responsive cells (Chokshi et al, 2019). Our work indicates that ipsilateral response depression may be more susceptible to changes in GLT1-mediated glutamate uptake.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, future work will be needed to clarify the mechanisms relating developmental synaptic refinement to particular subsets of synapses, the role of astrocytes and GLT1, and the microstructure of the tripartite synapse. (Chokshi, Druciak, Worley, & Lee, 2019). Our work indicates that ipsilateral response depression may be more susceptible to changes in GLT1-mediated glutamate uptake.…”
Section: Discussionmentioning
confidence: 60%
“…It is possible that distinct cellular mechanisms differentially regulate contralateral and ipsilateral responses and plasticity. For example, it has recently been shown that Homer1a specifically and actively establishes the contralateral bias intrinsic to binocular‐responsive cells (Chokshi, Druciak, Worley, & Lee, 2019). Our work indicates that ipsilateral response depression may be more susceptible to changes in GLT1‐mediated glutamate uptake.…”
Section: Discussionmentioning
confidence: 99%